The Effect of Work Flexibility and Stress on the Performance of Civil Servants during the Covid-19 Pandemic (Study on Employees Aceh Watershed Department) - Shelly Kurniawan; Demson Tiopan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Intellectual property is not only beneficial for the creator, but also the community as users of products and/or services protected by intellectual property. The more intellectual property created, the better for legal subjects or business entities that are legal entities or not legal entities because they can increase the intellectual capital value of the person and/or company. The author's purpose in analyzing this is to qualitatively examine the relationship between intellectual property and the addition of the intellectual capital value of a company and whether some changes in the regulations in Law Number 11 of 2020 concerning Job Creation can affect the intellectual capital of a company. This research method is normative juridical which will explore some secondary literature, which consists of Law Number 11 of 2020 concerning Job Creation, laws and regulations related to intellectual property, books, journals, and papers related to intellectual property and intellectual capital. Research shows that the more intellectual property owned by a company that is sold in the community can increase the intellectual capital of a company. Changed arrangements related to patents and trademarks in Law Number 11 of 2020 concerning Job Creation can affect the company's intellectual capital in terms of capital structure and changes to the regulation on patent implementation can increase intellectual capital for all categories, namely human capital, structure capital, and physical /customer capital.